Perceptions of dental healthcare providers about gender based violence in Maharashtra, India - M., Aby Mathews; Kathavate, Rohini N.; Bendale, Abhishek S.; Kumar, Disha (International Journal Of Community Medicine And Public Health, 2017)
Background: To assess the level of knowledge and preparedness that the dental practitioners of Maharashtra, India posses in terms of identifying, analyzing, treating and supporting a potential victim of gender based violence (GBV). This study also aims to analyse the present level of confidence the dental fraternity has in the educational, legal and law enforcement systems of India in terms of dealing with GBV issues. Methods: A descriptive cross sectional study involving an anonymous electronic survey of a sample of 156 dental practitioners practicing in Maharashtra India. The survey was designed with two sections. The first section of the survey was designed to collect the demographic data of the respondents and information about their professional background. The second section comprised of 20 questions analysing the respondents level of understanding of the concept of GBV, their familiarity with GBV in practice, their opinion of current education and legal system concerning to GBV issue and their intent to further study in the subject. Results: The response rate was 75.6% and 118 responses were received. Out of the 118 responses, 17 were incomplete and were excluded from the study. Thus only 101 responses were used for analysis. More than 35% of the respondents were aware of the concept of GBV where as almost 20% were completely new to the subject. More than 75% agreed that GBV affects both genders and affects primarily females. More than 80% responded that the victims generally do not tend to disclose who abused them. Majority agreed on the fact that the victims tend to confide with their family and friends other than any other option when affected by GBV. 50% of respondents were confident that they could handle a case of GBV in their clinic effectively. 72.7% responded that they were not aware of the Guidelines & Protocols, Medico-legal care for survivors/ victims of sexual violence, Ministry of health and family welfare, Government of India. More than 40% logged an increase in understanding of GBV after reading the snapshot of Guidelines & Protocols provided with the survey and expressed interest to learn more. 64.6% noted that they were not properly equipped for handling a GBV case but hope to do better with proper trainings. Regarding the present legal system, 54.3% of the respondents categorised it as mature but non-prompt. More than 80% agreed that there should be incorporation of modules on GBV in the academic curriculum and 96% logged interest in having more information on GBV sent to them. Conclusions: Even though there was a consensus among the respondents that females were the primary victims of gender based violence, the study showed that there is only moderate awareness regarding Gender Based Violence amongst the dental practitioners in the state of Maharashtra. Even though a majority of the respondents were not aware of the proper guidelines and protocols for handling a case of GBV, a little over 50% were convinced that they would be able to handle a case of GBV in their practice. A need to update the curriculum and provide the currently practicing dentists with proper training was also identified.